On a class of univalent functions - Dinggong Yang; Jinlin Liu (International Journal of Mathematics and Mathematical Sciences)
We consider the class of univalent functions defined by the conditions f(z)/z≠0 and |(z/f(z))′​′|≤α,|z|<1, where f(z)=z+⋯ is analytic in |z|<1 and 0<α≤2.